(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Wireless power transfer (WPT) has emerged as a transformative technology, enabling the transmission of electrical energy without physical connectors. This abstract explores the primary technologies driving WPT, including inductive coupling, magnetic resonance coupling, and radio-frequency transmission. Each method’s underlying principles, advantages, and limitations are examined. The paper also discusses current standards governing WPT systems and highlights diverse applications across industries such as consumer electronics, healthcare, and automotive sectors. Furthermore, the challenges faced in terms of efficiency, distance, and safety are outlined, alongside future research directions aimed at enhancing performance and expanding the practical uses of WPT.